Literature Review : Penggunaan Machine Learning Berbasis SVM untuk Klasifikasi Penyakit Diabetes - Adih Adih; Wahyu Aji Dwi Pangestu; Muhamad Fauzi Akbar; Purnamasari Purnamasari; Farlin Wabula; Ines Heidiani Ikasari (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
Diabetes is one of the diseases that poses a significant global health challenge, with a considerable impact on quality of life and mortality rates. This study examines the use of the Support Vector Machine (SVM) algorithm for diabetes classification through a literature review. SVM was chosen due to its ability to handle imbalanced and complex data. The aim of this study is to assess the effectiveness of SVM compared to other machine learning methods in detecting diabetes. The results of the literature review indicate that SVM achieves higher accuracy than other methods such as Naïve Bayes and Decision Tree, with some studies showing accuracy above 90%. This study is expected to provide deeper insights into the development of machine learning-based diagnostic systems for diabetes.